1997
DOI: 10.1128/iai.65.2.640-644.1997
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunization with PspA elicits protective humoral immunity against Streptococcus pneumoniae infection

Abstract: Streptococcus pneumoniae is a major respiratory mucosal pathogen affecting infants and children. Although a polysaccharide-based vaccine has been useful in adult populations, it does not elicit protective immunity in infants and young children. Pneumococcal surface protein A (PspA) is a highly immunogenic surface protein produced by all strains of Streptococcus pneumoniae. Previous studies have shown that systemic immunization of mice with PspA can elicit protective immunity against fatal pneumococcal infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 29 publications
(47 reference statements)
0
16
0
2
Order By: Relevance
“…Since mucosal (e.g. nasal or oral) administration of CT with soluble protein has proven to be an effective regimen for the generation of antigen‐specific antibody responses (20, 28, 30, 45, 47), we next examined the effect of the transcutaneous administration of CT as adjuvant on 40 K‐OMP‐specific antibody responses. Rats transcutaneously immunized with 40k‐OMP plus CT showed almost the same 40k‐OMP‐specific serum IgG and IgA responses as those immunized with 40k‐OMP alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since mucosal (e.g. nasal or oral) administration of CT with soluble protein has proven to be an effective regimen for the generation of antigen‐specific antibody responses (20, 28, 30, 45, 47), we next examined the effect of the transcutaneous administration of CT as adjuvant on 40 K‐OMP‐specific antibody responses. Rats transcutaneously immunized with 40k‐OMP plus CT showed almost the same 40k‐OMP‐specific serum IgG and IgA responses as those immunized with 40k‐OMP alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that TCI with 40k‐OMP alone elicited significant serum responses as well as salivary IgG responses. Normally, protein antigen given via the mucosal route without adjuvant has been generally reported to be only a weak immunogen (28, 45–47) and therefore, has been presumed to require a mucosal adjuvant such as CT to induce antigen‐specific antibody responses (28, 31, 45, 47). Our previous findings also indicated that nasal delivery of 40k‐OMP with CT as an adjuvant induced 40k‐OMP‐specific Th2‐type responses that in turn led to the induction of serum IgG and IgA as well as salivary IgA antibodies (30, 31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mononuclear cells were obtained at the interface of the 50% and 75% layers of a discontinuous Percoll gradient (GE Healthcare UK, Ltd, Little Chalfont, Buckinghamshire, UK) (Maeba et al ., ). To assess the numbers of antigen‐specific AFCs, an enzyme‐linked immunospot (ELISPOT) assay was performed as described previously (Yamamoto et al ., ). Briefly, 96‐well nitrocellulose plates (BD Biosciences, Franklin Lakes, NJ) were coated with 25k‐hagA‐MBP (5 μg mL −1 ), incubated at 4 °C for 20 h, and then washed extensively before being blocked with RPMI‐1640 containing 10% fetal calf serum.…”
Section: Methodsmentioning
confidence: 97%
“…Previous studies have demonstrated the efficacy of mucosal immunization for delivering vaccines, which induces mucosal and systemic immune responses via oral (Yamamoto et al ., ; Liu et al ., ), nasal (Koizumi et al ., ; Momoi et al ., ), and sublingual routes (Cuburu et al ., ; Song et al ., ; Zhang et al ., ). Of the vaccination methods available, sublingual vaccination has recently been reported to induce significant antibody (Ab) production in nasal, bronchial, and oral mucosa (Cuburu et al ., ; Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 99%